Atmospheric dispersion and dose assessment of 137Cs and 131I from hypothetical incidents of nuclear power plant in Southeast Asia - L.H., Muhamad; M.K., A Karim; Chew, Ming Tsuey *; M.M.A., Kechik; N.M., Shah; M.J., Ibrahim; Saeed, I.M. (Elsevier, 2023)
In the event of radiological incidents, specifically nuclear accidents, a substantial quantity of radionuclides may be distributed, resulting in potential cancer hazards and the possibility of death. Hence, it is imperative for governing bodies to replicate hypothetical accidents that may occur from potential nuclear reactors, with the aim of ascertaining the probable dose exposure that the populace may face. The aim of this study was to evaluate the level of dispersion of 131I and 137Cs that would ensue from a hypothetical incident scenario of a nuclear power plant (NPP) in Ninh Thuan, Vietnam, and Mersing, Malaysia, by utilizing the HYSPLIT model. The model was set up based on the meteorological conditions in the potential site for NPP located in Southeast Asia. Following the study, a comparison was made between the results and the authorized dose limits proposed by the International Atomic Energy Agency to assess the potential mortality risk arising from an accident. The outcomes revealed that the mean activity concentration for both radionuclides was greater in Mersing than in Ninh Thuan on the initial day of the accident. The activity concentration of 137Cs and 131I at Mersing is the highest at 3.34 × 102 kBq/m3 and 2.01 × 104 kBq/m3, respectively. Meanwhile, Ninh Thuan has the highest activity concentration of 137Cs and 131I at 2.37 × 102 kBq/m3 and 1.43 × 104 kBq/m3, respectively. Based on these figures, the release of 137Cs and 131I at Mersing results in an effective dose of approximately 2.58 × 10